Serum anti-Müllerian hormone (AMH) concentration during pregnancy: a longitudinal study - Sarah McCredie; Belinda An; Monika McShane; William Ledger; Christos A Venetis (Bioscientifica, 2023)
A prospective longitudinal cohort study aimed to longitudinally examine the kinetics of anti-Müllerian hormone (AMH) during the first two trimesters of pregnancy. Pregnant women with stored first-trimester serum samples were recruited at 24-28 weeks gestation during their gestational diabetes testing, where they provided an additional serum sample. The samples were analysed for AMH, oestradiol and progesterone concentrations. A decrease in serum AMH was observed in 40 out of 45 (88.9%) (95% CI: 75.9-96.3%) of the participants in this study. The median serum AMH concentration was 10.9 pmol/L in the first trimester and 6.5 pmol/L during the second trimester, with a significantly different distribution of the values between the first-trimester and the second-trimester AMH samples (P < 0.001). The median percentage of AMH difference of −39.8%. This study demonstrated a significant decrease in serum AMH levels from the first to the second trimester of pregnancy. The absolute decrease in AMH levels seems to be positively associated with first-trimester AMH levels, whereas the percentage of AMH difference is not. Further studies are required to elucidate the potential physiological mechanisms of this finding.